2020
DOI: 10.36348/sjef.2020.v04i10.003
|View full text |Cite
|
Sign up to set email alerts
|

Using UTAUT Model to Predict Social Media Adoption among Indonesian SMEs

Abstract: The purpose of this paper was to predict the factors that influence the adoption of Social Media Apps (SMA) among Indoneisan SMEs to promote and market their business using UTAUT (Unified Theory of Acceptance and Use of Technology theory) approach. These factors include performance expectancy, effort expectancy, social influence, and facilitating conditions. To fulfill these aims, a quantitative research was adopted. Data were taken using a questionnaire from total of 162 respondents, namely the owner or manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
3
11
1
Order By: Relevance
“…That is why the respondent refer to it as the highest among the variables given. According to Abdat (2020) that performance expectancy refers to as the degree in which users believe that using a new technology or system will help them accomplish tasks better. Furthermore, it was found that performance expectancy along with social influence and effort expectancy are significant predictors of users' behavior intention in using web-based services.…”
Section: Resultsmentioning
confidence: 99%
“…That is why the respondent refer to it as the highest among the variables given. According to Abdat (2020) that performance expectancy refers to as the degree in which users believe that using a new technology or system will help them accomplish tasks better. Furthermore, it was found that performance expectancy along with social influence and effort expectancy are significant predictors of users' behavior intention in using web-based services.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two studies demonstrate that performance expectancy has a significant positive effect on MSMEs’ intention to adopt information and communications technology (e.g. social media) (Abdat, 2020; Rodrigues et al , 2016). Previous research also illustrates that effort expectancy plays a pivotal role in new technology acceptance (Rodrigues et al , 2016; Rozmi et al , 2019; Venkatesh et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also illustrates that effort expectancy plays a pivotal role in new technology acceptance (Rodrigues et al , 2016; Rozmi et al , 2019; Venkatesh et al , 2012). As for social influence, studies have shown that it is a direct determinant of behavioral intention to adopt new technology (Abdat, 2020; Rozmi et al , 2019). Finally, past research indicates that the perceived availability of technical and organizational resources (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, those involved in research works in this field have further agreed that social influence is an essential factor in the process of accepting new technologies (Cheung et al, 2011). For instance, a study conducted by Abdat (2020) has found that social influence significantly impacts the adoption of social media apps among Indonesian small and medium-sized enterprises. Nonetheless, an empirical study on the adoption of e-commerce in the SME sector by Punjab by Batra and Arora (2020) also revealed that social influence was a significant determinant.…”
Section: Social Influencementioning
confidence: 99%